KAJIAN HUKUM DAN TINDAKAN BAGI PELANGGARAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Sulistyani Eka Lestari (universitas islam darul ulum lamongan, 2017)
Livestock waste as a negative factor on the farm is a phenomenon that can not be removed easily. On land, livestock waste can weaken the carrying capacity of the soil, causing soil pollution. While on the water, microorganisms pathogenic (disease causing) derived from livestock waste will pollute the marine environment. In addition, pollution of water, air and soil are also cases of pollution and environmental destruction that stand out as a result of rapid activity less maintain the aspect preservation of the environment. The issue of environmental pollution can be solved through medical aspects, planalogis, technological, environmental engineering, economics and law. In the perspective of environmental law, the completion of cases of environmental pollution environment includes three (3) fields at once, namely legal administrative environment, legal environment of civil and environmental law penal law as a logical consequence of the position of environmental law as the law is functional, thus, in terms of substance, job descriptions environmental law consists of: environmental law administrative, civil environmental law, environmental law penal law. Law No. 32 of 2009 on the Protection and Environmental Management delegate authority from central to local government which is to optimize the role of local governments in a bureaucratic environment ministry.